Scalable Fabrication of Methylammonium-Free Wide-Bandgap Perovskite Solar Cells by Blade Coating in Ambient Air - Liu, Jianbo; Zhang, Meng; Sun, Xiaoran; Xiang, Linhu; Yang, Xiangyu; Hu, Xin; Wang, Zhicheng; Hou, Tian; Qin, Jinzhao; Huang, Yuelong; Abdi‑Jalebi, Mojtaba; Hao, Xiaojing (Nano-Micro Letters, 2025)
Scalable fabrication of efficient wide-bandgap (WBG) perovskite solar cells (PSCs) is crucial to realize the full commercial potential of tandem solar cells. However, there are challenges in fabricating efficient methylammonium-free (MA-free) WBG PSCs by blade coating, especially its phase separation and films stability. In this work, an MA-free WBG perovskite ink is developed for preparing FA0.8Cs0.2Pb(I0.75Br0.25)3 films by blade coating in ambient air. Among various A-site iodides, RbI is found to be the most effective in suppressing the precipitation of PbI2 induced by Pb(SCN)2 while keeping the enlarged grains. The distribution of Rb suggested that the Rb ions are kept isolated with the perovskite grains during the crystallization and Ostwald ripening processes, which contributes to the formation of the large-grain WBG perovskite film with minimum non-radiative recombination. As a result, a power conversion efficiency (PCE) of 23.0% was achieved on small-area WBG PSCs, while mini-modules with an aperture area of 10.5 cm2 exhibited a PCE of 20.2%, among the highest reported for solar cells prepared with WBG perovskites via blade coating. This work presents a scalable and reproducible fabrication strategy for stable MA-free WBG PSCs under ambient conditions, advancing their path toward commercialization. Highlights: 1 RbI is the most effective in mitigate PbI2 precipitation caused by Pb(SCN)2 while maintaining large grains. 2 Rb is kept at the grain boundaries during crystallization and Ostwald ripening, contributes to a slow growth of the grains. 3 Wide-bandgap perovskite solar cells with blade-coated perovskite in air achieved a certified power conversion efficiency of 23%, among the highest values reported.